We Appreciate Power: A Multimodal Critical Discourse Analysis of Grimes' Music Video Posted on YouTube - Enguídanos Gómez, Adrià (Université autonome de Barcelone, 2019)
The aim of this dissertation is to produce a multimodal critical discourse analysis of Grimes' video We Appreciate Power. This will serve to explore issues of ideology, identity and multilingualism in both the music video and the YouTube polylogues generated in the same web page. In this work I suggest that Grimes adopts a poststructuralist view that inherits Haraway's cyborg concept (1991) in this piece of multimedia. I claim that Grimes wanted to show the conflictive moral boundaries that the idea of the cyborg and trans-humanism casts upon Western civilization, such as the loss of free will but also the transgression of problematic dichotomies. The fact that the comment section of the video is available to use might signal that Grimes wanted to raise awareness about trans-humanism. By doing virtual ethnography research, examples of discussion about the relationship between the video and the studied polylogues will be examined regarding the notions of the cyborg and multilingualism.

On the Internet by Means of Popular Music: The Cases of Grimes and Childish Gambino - Ohlendorf, Kristopher R. K. (Université Western Ontario, 2016)
What is the internet? It began as a military research experiment, but the internet has since become a sweeping cultural phenomenon. One of the most prevalent areas of the internet’s cultural dominance is in popular music, and this thesis addresses how the internet is being understood and discussed by popular music artists. I study the works of Grimes and Childish Gambino, two popular music artists who grew up alongside the internet’s rise to cultural dominance and explicitly address this experience as an integral component of their lives and works. I look specifically at discourse surrounding Grimes’ “post-internet” music and Childish Gambino’s expansive conceptual work Because the Internet (2013). This research concludes by addressing how popular music artists like Grimes and Childish Gambino are helping produce the ways in which we understand and discuss the cultural phenomenon of the internet, and how they provide a foundation for future artists and research to build upon.

Cross-dressing to Backbeats: An Exploration of the Practices, Wo/men Producers, and History of Electroclash - Madden, David (Université Concordia, 2013)
This research-creation dissertation focuses on the emergence of electroclash as a dominant form of electronic dance music in the late 1990s and early 2000s. Electroclash combines the extended pulsing sections of techno, house and other dance musics with the trashier energy of rock and new wave. The genre signals an attempt to reinvigorate dance music with a sense of sexuality, personality and irony. Electroclash also emphasizes, rather than hides, the European, trashy elements of electronic dance music. This project addresses the following questions: what is distinct about the genre and its related practices, both in and out of the studio? Why do rock and electro come together at this point and in this way? Why is electroclash affectively powerful for musicians, audiences and listeners? And, what does the genre portend in terms of our understandings of the politics of electronic music? The coming together of rock and electro is examined vis-à-vis the ongoing changing sociality of music production/distribution and the changing role of the producer. Numerous women, whether as solo producers or in the context of collaborative groups, significantly contributed to shaping the aesthetics and production practices of electroclash, an anomaly in the history of popular music and electronic music where the role of the producer has typically been associated with men. These changes are discussed in relation to the way key electroclash producers often used a hybrid approach to production involving the integration of new(er) technologies, such as laptops containing various audio production software with older, inexpensive keyboards, microphones, samplers and drum machines to achieve the ironic backbeat laden hybrid electro-rock sound.

Crossdressing to Backbeats: The Status of the Electroclash Producer and the Politics of Electronic Music - Madden, David (Dancecult, 2012)
Addressing the international emergence of electroclash at the turn of the millenium, this article investigates the distinct character of the genre and its related production practices, both in and out of the studio. Electroclash combines the extended pulsing sections of techno, house and other dance musics with the trashier energy of rock and new wave. The genre signals an attempt to reinvigorate dance music with a sense of sexuality, personality and irony. Electroclash also emphasizes, rather than hides, the European, trashy elements of electronic dance music. The coming together of rock and electro is examined vis-à-vis the ongoing changing sociality of music production/distribution and the changing role of the producer. Numerous women, whether as solo producers, or in the context of collaborative groups, significantly contributed to shaping the aesthetics and production practices of electroclash, an anomaly in the history of popular music and electronic music, where the role of the producer has typically been associated with men. These changes are discussed in relation to the way electroclash producers Peaches, Le Tigre, Chicks on Speed, and Miss Kittin and the Hacker often used a hybrid approach to production that involves the integration of new(er) technologies, such as laptops containing various audio production softwares with older, inexpensive keyboards, microphones, samplers and drum machines to achieve the ironic backbeat laden hybrid electro-rock sound.